Word Recognition among PSU College Students - Sison, Marissa E. (Asian Journal of Multidisciplinary Studies, 2018)
This study intended to determine the level of ability of 43 freshman Bachelor of Arts in English Language students in in Pangasinan State University in word recognition who were selected through complete enumeration. The level of ability in word recognition was measured by an instrument which was adapted. The word recognition covered in this study were function and content words. Findings showed that the freshman AB in English Language students are very good in recognizing content words but good in recognizing function words. The overall level of ability of the respondents in recognizing both word classes is very good. Therefore, students are encouraged to continuously study the different word classes to strengthen their ability in recognizing words according to their classes.